Hypoxia inducible factor 1 (HIF-1) and cardioprotection - Tekin Demet; Dursun Ali D; Xi Lei (Acta Pharmacologica Sinica, 2016)
Since its discovery in early 1990s, hypoxia inducible factor 1 (HIF-1) has been increasingly recognized for its key role in transcriptional control of more than a hundred genes that regulate a wide-spectrum of cellular functional events, including angiogenesis, vasomotor control, glucose and energy metabolism, erythropoiesis, iron homeostasis, pH regulation, cell proliferation and viability. Evidence accumulated during the past 7 years suggests a critical role for HIF-1α in mediating cardioprotection. The purpose of our present article is to provide an updated overview on this important regulator of gene expression in the cellular stress-responsive and adaptive process. We have particularly emphasized the involvement of HIF-1 in the induction of cardioprotective molecules, such as inducible nitric oxide synthase (iNOS), hemeoxygenase 1 (HO-1), and erythropoietin (EPO), which in turn alleviate myocardial damages caused by harmful events such as ischemia-reperfusion injury. Despite these advances, further in-depth studies are needed to elucidate the possible coordination or interaction between HIF-1α and other key transcription factors in regulating protein expression that leads to cardioprotection.